Some Characteristics of Neurons in the Reticular Nucleus of the Thalamus - Z. I. Nanobashvili; I. G. Bilanishvili; M. G. Barbakadze; N. A. Khizanishvili (Current Progress in Medicine and Medical Research Vol. 6, 2023)
The results of this study demonstrate, for the first time, that generation of spike potentials of different amplitudes was observed in the activity of the thalamic reticular nucleus neurons. The generation of one action potential does not interfere with the generation of another, and a spike potential of smaller amplitude can occur at the ascending or descending phase of the spike potential of large amplitude. It can be argued that the spike potentials of lower amplitudes arising in the thalamic reticular nucleus neuron are of dendritic origin. Given both the strategic position and the functional purpose of the NRT, it can be assumed that the neurons of this structure must each time be discharged with spike potentials in order to carry out their modulating effect on other areas of the nervous system of the brain without leakage.